Pengaruh Temperatur Tempat Tidur Terhadap Tubuh Fungsi Pemulihan Kecepatan Terhadap Bedah Posting - tri trinataliswati; Gunawan . (Jurnal Keperawatan Terapan, 2019)
Basically treatment is preoperative patient care, intra and postoperative surgical cases. In postoperative care there is currently a technical problem that remains unanswered, namely heating the bed postoperatively. Implementation of early mobilization, effective coughing, relaxation still requires effective participation of nurses and patients are sometimes ignored because it is too time consuming and nurses. Heating the bed according to the researchers seems to be the solution above. The purpose of this study was to determine the effect of bed temperature on the speed of recovery of body function (peristaltic / platinum movement) using quasi experimental research methods to approach post control design, with a sample of 15 groups of 15 control treatment groups, sampling with simple random sampling technique, research done in the Inpatient Room of Bogenvil Ngudi Waluyo Wlingi Hospital. The results obtained by the t test, t is 3.24 are greater than t table. In conclusion there is a significant effect of bed temperature on postoperative speed of body function (peristaltic / platelet movement) recovery. This evidence should be an encouragement to manage the implementation of surgical care for habits.